Encouragement of Educators for SDG 4: An Investigation into Lesson Study-Based Peer Supervision - Indah Aminatuz Zuhriyah; M. Aqil Fahmi Sanjani; Itsna Nur Laili; Salahuddin Salahuddin (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the role of collaborative supervision based on lesson study in enhancing teacher professionalism and improving learning quality in alignment with global educational priorities such as SDG 4 promoted by the United Nations. The background of this research is grounded in the persistent limitations of traditional supervisory practices, which tend to be hierarchical and evaluative rather than developmental. This study employed a qualitative case study design, involving classroom observations, in-depth interviews with teachers, and document analysis. Data were analyzed using thematic analysis to identify patterns across supervisory practices and instructional improvement. The findings reveal that multi-directional collaboration fosters professional dialogue and shared responsibility among teachers and school leaders. Furthermore, the integration of the lesson study cycle (Plan–Do–See) into supervision creates a systematic and continuous process of professional learning. Additionally, the shift toward a learning-centered focus enables teachers to better understand student engagement and learning processes. Evidence-based practices also demonstrate measurable improvements in learning quality, including student participation and instructional variation. These findings contribute to the development of a comprehensive supervision model that integrates collaboration, systematic cycles, and data-driven practices.